2020
DOI: 10.1111/luts.12324
|View full text |Cite
|
Sign up to set email alerts
|

GreenLight HPS laser 120 W vs diode laser 300 W vaporization of the prostate for the treatment of benign prostatic hyperplasia in Japanese patients: A prospective, single‐center, randomized clinical trial

Abstract: Objectives: This study aimed to compare the safety and efficacy of laser vaporization with 532 nm GreenLight High Performance System (HPS) laser 120 W (PVP) and 980 nm diode laser 300 W (CVP) for the treatment of benign prostatic hyperplasia (BPH) in a prospective, single-center, randomized clinical trial. Methods: A total of 153 consecutive patients with symptomatic BPH were included; 79 patients were treated with PVP and 74 with CVP. Patients were assessed preoperatively and at 3, 6, and 12 months postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
2
7
2
Order By: Relevance
“…The perioperative and postoperative complications observed in this study are in line with previous reports. 1,2,5,6,7,10,17 Our study confirmed the absence release of bladder outlet obstruction. The rate of epididymitis after DVP was reported to be higher than PVP in previous studies 6 ; however, this study found no significant difference between DVP, PVP, and ThuVAP during follow-up.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The perioperative and postoperative complications observed in this study are in line with previous reports. 1,2,5,6,7,10,17 Our study confirmed the absence release of bladder outlet obstruction. The rate of epididymitis after DVP was reported to be higher than PVP in previous studies 6 ; however, this study found no significant difference between DVP, PVP, and ThuVAP during follow-up.…”
Section: Discussionsupporting
confidence: 83%
“…The feasibility of laser ablation for BPH on anticoagulants was elucidated by previous studies. 6,15,16 During this trial, PVP, DVP, and ThuVAP were all performed without severe complications in patients on anticoagulants, suggesting a favorable safety profile for all of these techniques even in high-risk patients.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…12 In addition, unlike in conventional surgery, in CVP, it is not necessary to suspend antithrombotic therapy during the perioperative period, so even if it is difficult to suspend treatment with anticoagulant or antiplatelet drugs due to arrhythmia or cerebrovascular disease, it is possible to perform transurethral surgery in patients under continued antithrombotic therapy. 13 Our prospective survey revealed the following points.…”
Section: Discussionmentioning
confidence: 94%